Influence of Graphene Powder on the Physio-Mechanical Properties of Jute Reinforced Epoxy Composites for Automobile Applications - Vishwas Mahesh; Vinyas Mahesh (Mechanics of Advanced Composite Structures)
Graphene was employed as filler in various formulations of jute fibers reinforced epoxy composites in this study. Graphene's influence on the physio-mechanical properties of epoxy-based polymer composite reinforced with jute was examined in terms of tensile strength, flexural strength, impact strength, hardness, and water absorption. It was found that the mechanical characteristics significantly improved. Also, a significant decrease in the proportion of water absorption was obtained. The optimal proportion of graphene filler in proposed composites is also discussed in the present study. The optimal concentration filler in the proposed composites was found to be 4%. The findings show that graphene is a promising material and graphene mixed with 36% jute in an epoxy-based composite effectively improves the composites' strength. The findings of this study demonstrate the potential of graphene powder in enhancing the physio-mechanical properties of jute-reinforced epoxy composites for automobile applications. The incorporation of graphene powder offers a promising route for the development of lightweight and sustainable materials that can meet the stringent requirements of the automotive industry in terms of strength, durability